Electricity capacity markets / Todd S. Aagaard,Villanova University Charles Widger School of Law, Andrew N. Kleit, The Pennsylvania State University (Energy and Environmental Economics). - Aagaard, Todd; Kleit, Andrew N. (Cambridge University Press, 2022)
Initially created as afterthoughts to competitive electricity markets, capacity markets were intended to enhance system reliability. They have evolved into massive, highly controversial, and poorly understood billion-dollar institutions. Electricity Capacity Markets examines the rationales for creating capacity markets, how capacity markets work, and how well these markets are meeting their objectives. This book will appeal to energy experts and non-experts alike, across a range of disciplines, including economics, business, engineering, public policy, and law. Capacity markets are an important and provocative topic on their own, but they also offer an interesting case study of how well our energy systems are meeting the needs of our increasingly complex society. The challenges facing capacity markets - harnessing market forces for social good, creating networks that manage complexity, and achieving sustainability - are very much core challenges for our twenty-first century advanced industrial society.